Contentious politics in the Maghreb: a comparative study of mobilization in Tunisia and Morocco - Roko, Johan Rognlie (AUC Knowledge Fountain, 2011)
This thesis sets out by exploring processes of socio-economic and political change leading up to the most recent upheavals in the Arab World, with a focus on Tunisia and Morocco. A comparative study of the different historical trajectories of these countries is useful to identify causes for variation between countries that share many cultural, historical, socio-economic, and also political characteristics. The thesis illustrates how these countries have liberalized their economies without liberalizing their polities to the same extent, a process that has undermined regime legitimacy gradually over many years. In Tunisia the worsening marginalization for growing segments of the population led to massive unrest. When exploring how such mobilization was possible under repressive conditions, I suggest that a combination of â traditionalâ mobilization by means of NGOs, and â newâ mobilization via social media produced powerful tools for channeling popular discontent, articulated as oppositional discourse. The visible political opportunities for protests in Tunisia were not many, but the new, shared discourses of alienation and indignation compelled people to act. In Morocco, contention has been a more moderate and drawn-out affair throughout the spring and summer of 2011. The thesis contrasts mobilization in these two countries, and suggests that differences in regime type, levels of socio-economic development and class configuration, as well as patterns of interaction between regimes and protesters, may explain most of the variation in how mobilization unfolded, and which concessions the state has yielded.